Brzoskwinia (Prunus persica [L.] Batsch) w antycznym i wczesnobizantyńskim lecznictwie według wybranych źródeł [I–VII w. n.e.] - Jagusiak, Krzysztof; Kokoszko, Maciej (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
The peach (Prunus persica [L.] Batsch) is a tree native to the region known today as Northwest China, where its fruits were known around 2000 BC. Inhabitants of the Mediterranean Area came into contact with the peach probably between the 6th and 4th century BC thanks to the contacts with Persian Empire. In the western part of the Mediterranean Region the peach appeared later (ca. 1st c. AD). In the period under study there were many varieties of the peach, and they were eaten in many different ways – e.g. raw, dried, boiled etc. They could be consumed without any other ingredients, or as an element of more complicated dishes. Ancient and early Byzantine authors, who wrote their treatises between the 1st and 7th c. AD, and dealt with medicine (Dioscorides, Pliny the Elder, Galen, Oribasius, Aetius of Amida, Paul of Aegina, Athimus and others), described dietetic properties of a peach with details. Moreover, they left some information about a medical use of this fruit. This aspect of their works is an element of a wider and well-known phenomenon, i.e. an important role of all groups of aliments in the ancient art of healing.